Structure and optical properties of ZnO:V thin films with different doping concentration - Wang Li-Wei (2009)
A series of ZnO thin films doped with various vanadium concentrations were prepared on glass substrates by direct current reactive magnetron sputtering. The results of the X-ray diffraction (XRD) show that the films with doping concentration less than 10 at.% have a wurtzite structure and grow mainly along the c-axis orientation. The residual stress, estimated by fitting the XRD diffraction peaks, increases with the doping concentration and the grain size also has been calculated from the XRD results, decreases with increasing the doping concentration. The surface morphology of the ZnO:V thin films was examined by SEM. The optical constants (refractive index and extinction coefficient) and the film thickness have been obtained by fitting the transmittance. The optical band gap changed from 3.12 eV to 3.60 eV as doping concentration increased from 1.8 at.% to 13 at.% mol. All the results have been discussed in relation with doping concentration